Overall assessment of alkali-silica reaction affected recycled concrete aggregate mixtures derived from construction and demolition waste. (April 2021) - Zhu, Yufeng; Zahedi, Andisheh; Sanchez, Leandro F.M.; Fournier, Benoit; Beauchemin, Sean
Abstract: A large amount of research has been conducted on the reuse of construction and demolition waste (CDW) in concrete. Yet, CDW may display pre-existing damage which raises concerns on its use. In this work, coarse recycled concrete aggregate (RCA) is reclaimed from distinct members of an alkali-silica reaction (ASR) affected overpass. RCA mixtures incorporating 50 and 100% replacement are then manufactured and stored in conditions enabling further ASR development. Mechanical (Stiffness Damage Test- SDT) and microscopic (Damage Rating Index- DRI) analyses are conducted at a fixed "secondary" induced expansion. Results indicate that the overall damage of ASR-affected RCA mixtures is different from conventional concrete and depends upon the "past" RCA condition. Furthermore, the DRI can capture the "past" and "secondary" expansion while the SDT simply detects the "secondary" distress. Finally, an adapted DRI version is proposed to better evaluate and distinguish "past" and "secondary" damage in ASR-affected recycled concrete.